Global Weak Solutions of the Navier-Stokes/Fokker-Planck/Poisson Linked Equations - Anoshchenko, O.; Iegorov, S.; Khruslov, E. (Журнал математической физики, анализа, геометрии, 2014)
We consider the initial boundary value problem for the linked Navier- Stokes/Fokker-Planck/Poisson equations describing the flow of a viscous incompressible fluid with highly dispersed infusion of solid charged particles which are subjected to a random impact from thermal motion of the fluid molecules. We prove the existence of global weak solutions for the problem and study some properties of these solutions.